NF-κB/STAT5/miR-155 network targets PU.1 in FLT3-ITD-driven acute myeloid leukemia - Gerloff, D (Leukemia, 2014)
Almost 30% of all acute myeloid leukemias (AML) are associated with an internal tandem duplication (ITD) in the juxtamembrane domain of FMS-like tyrosine kinase 3 receptor (FLT3). Patients with FLT3-ITD mutations tend to have a poor prognosis. MicroRNAs (miRNAs) have a pivotal role in myeloid differentiation and leukemia. MiRNA-155 (MiR-155) was found to be upregulated in FLT3-ITD-associated AMLs. In this study, we discovered that FLT3-ITD signaling induces the oncogenic miR-155. We show in vitro and in vivo that miR-155 expression is regulated by FLT3-ITD downstream targets nuclear factor-κB (p65) and signal transducer and activator of transcription 5 (STAT5). Further, we demonstrate that miR-155 targets the myeloid transcription factor PU.1. Knockdown of miR-155 or overexpression of PU.1 blocks proliferation and induces apoptosis of FLT3-ITD-associated leukemic cells. Our data demonstrate a novel network in which FLT3-ITD signaling induces oncogenic miR-155 by p65 and STAT5 in AML, thereby targeting transcription factor PU.1.